Differentially expressed genes related to oxidoreductase activity and glutathione metabolism underlying the adaptation of Phragmites australis from the salt marsh in the Yellow River Delta, China - Zhang, Liwen; Chen, Lin; Lu, Feng; Liu, Ziting; Lan, Siqun; Han, Guangxuan (PeerJ (San Francisco, CA), 2020)
The common reed ( Phragmites australis ) is a dominant species in the coastal wetlands of the Chinese Yellow River Delta, where it tolerates a wide range of salinity. Recent environmental changes have led to the increase of soil salinity in this region, which has degraded much of the local vegetation. Clones of common reeds from the tidal marsh may have adapted to local high salinity habitat through selection on genes and metabolic pathways conferring salt tolerance. This study aims to reveal molecular mechanisms underlying salt tolerance in the tidal reed by comparing them to the salt-sensitive freshwater reed under salt stress. We employed comparative transcriptomics to reveal the differentially expressed genes (DEGs) between these two types of common reeds under different salinity conditions. The results showed that only three co-expressed genes were up-regulated and one co-expressed gene was down-regulated between the two reed types. On the other hand, 1,371 DEGs were exclusively up-regulated and 285 DEGs were exclusively down-regulated in the tidal reed compared to the control, while 115 DEGs were exclusively up-regulated and 118 DEGs were exclusively down-regulated in the freshwater reed compared to the control. From the pattern of enrichment of transcripts involved in salinity response, the tidal reed was more active and efficient in scavenging reactive oxygen species (ROS) than the freshwater reed, with the tidal reed showing significantly higher gene expression in oxidoreductase activity. Furthermore, when the reeds were exposed to salt stress, transcripts encoding glutathione metabolism were up-regulated in the tidal reed but not in the freshwater reed. DEGs related to encoding glutathione reductase (GR), glucose-6-phosphate 1-dehydrogenase (G6PDH), 6-phosphogluconate dehydrogenase (6PD), glutathione S-transferase (GST) and L-ascorbate peroxidase (LAP) were revealed as especially highly differentially regulated and therefore represented candidate genes that could be cloned into plants to improve salt tolerance. Overall, more genes were up-regulated in the tidal reed than in the freshwater reed from the Yellow River Delta when under salt stress. The tidal reed efficiently resisted salt stress by up-regulating genes encoding for oxidoreductase activity and glutathione metabolism. We suggest that this type of common reed could be extremely useful in the ecological restoration of degraded, high salinity coastal wetlands in priority.